Knowledge, attitudes and practices about vaccination in Trentino, Italy in 2019. Issue 1 (2nd January 2021) - Melot, Bénédicte; Bordin, Paola; Bertoni, Caterina; Tralli, Valentina; Zuccali, Mariagrazia; Grignolio, Andrea; Majori, Silvia; Ferro, Antonio
ABSTRACT: Introduction : Vaccination is among the most important areas of progress in the worldwide history of public health. However, a crescent wave of anti-vaccine groups has grown in Western countries, especially in Italy, in the last two decades. Our aim was to evaluate adult's hesitancy and knowledge about vaccines and related diseases in Trentino-Alto Adige -the Italian region with the lowest vaccination coverages. Methods : We administered self-answered structured questionnaires in three malls in the Trentino province in June 2019. We collected demographic data and information on knowledge about vaccines, infectious diseases and attitude in seeking health information. We utilized a descriptive and multivariate analysis to investigate factors associated with vaccine hesitancy. Results : We collected 567 questionnaires, 18% of the people interviewed were hesitant toward vaccination and 16% were against mandatory vaccination. In the multivariate analysis a poor level of information, being younger than 60 years and being against compulsory vaccination were associated with vaccine hesitancy. Regarding information about vaccines, 76.5% of the people relied on physicians, and/or 49% navigated the internet, while social media are used by 16% of the study population. Though 41.5% searched information on official sites, only 14% knew the website VaccinarSì and 4.7% had visited it. Discussion : Compared to a previous study conducted in all of Italy except Trentino Alto Adige, the level of vaccination hesitancy was higher. It is important to utilize health professionals, the internet and especially social media to spread scientific information about vaccination.